Rifjagarðar í Bakkaflóa - landmótun, setgerð og myndun - Margrét Mjöll Benjamínsdóttir 1995- (2021)
Ice streams are fast flowing arteries of ice sheets and are known to have drained the Icelandic ice sheet during the last glacial period. Landforms including transverse ridges in former ice stream tracks can give vital information on ice stream dynamics and basal conditions. This study describes the sedimentology and morphology of transverse ridges in Miðfjörður in north-east Iceland. Methods used in this study include a ten-day field work where vertical profiles were investigated, fabric measurements conducted, and samples collected for analyzing grain-size distribution and clast morphology. Geomorphological mapping reveals 53 transverse ridges on the Miðfjarðartunga lowland that vary in size. Drumlins indicating the flow direction of the ice stream towards the north-east are found west of the study area and on the Miðfjarðarheiði highlands and raised shorelines of late Younger Dryas to early Preboreal age are seen below the ridge field. The interior of the ridges is dominated by a homogenous till that lacks deformation structures but includes occasional lenses of sorted sediments, possibly indicating liquification of the till during basal sliding. Clasts with orientation transverse to the ice flow, indicate increasing effective stress during time of formation. Increasing stress is the result of increased friction at the ice stream bed, suggesting a slowdown of the ice stream. A process that may have contributed to increased stress on the ice stream bed is basal freezing. Basal freezing occurred in the upper parts of the ice stream while the lower part was still streaming. Due to velocity differences, transverse crevasses would have formed in the transition zone between these two parts of the ice stream. The crevasses reached the glacier bed as the ice stream got thinner resulting in reconstruction of the subglacial till in to transverse ridges. This process is suggested to have contributed to the shutdown of the ice stream. This research and others alike, can be used to study modern ice streams and are also an ...